Effect of the Essential Oils of Bursera morelensis and Lippia graveolens and Five Pure Compounds on the Mycelium, Spore Production, and Germination of Species of Fusarium - Yoli Mariana Medina-Romero; Mario Rodriguez-Canales; Marco Aurelio Rodriguez-Monroy; Ana Bertha Hernandez-Hernandez; Norma Laura Delgado-Buenrostro; Yolanda I. Chirino; Tonatiuh Cruz-Sanchez; Carlos Gerardo Garcia-Tovar; Maria Margarita Canales-Martinez (Journal of Fungi, 2022)
The genus Fusarium causes many diseases in economically important plants. Synthetic agents are used to control postharvest diseases caused by Fusarium, but the use of these synthetic agents generates several problems, making it necessary to develop new alternative pesticides. Essential oils can be used as a new control strategy. The essential oils of Bursera morelensis and Lippia graveolens have been shown to have potent antifungal activity against Fusarium. However, for the adequate management of diseases, as well as the optimization of the use of essential oils, it is necessary to know how essential oils act on the growth and reproduction of the fungus. In this study, the target of action of the essential oils of B. morelensis and L. graveolens and of the pure compounds present in the essential oils (carvacrol, p-cymene, α-phellandrene, α-pinene, and Υ-terpinene) was determined by evaluating the effect on hyphal morphology, as well as on spore production and germination of three Fusarium species. In this work, carvacrol was found to be the compound that produced the highest inhibition of radial growth. Essential oils and pure compounds caused significant damage to hyphal morphology and affected spore production and germination of Fusarium species.